Novel Ag@Nitrogen-doped Porous Carbon Composite with High Electrochemical Performance as Anode Materials for Lithium-ion Batteries - Chen, Yuqing; Li, Jintang; Yue, Guanghui; Luo, Xuetao (Nano-Micro Letters, 2017)
A novel Ag@nitrogen-doped porous carbon (Ag-NPC) composite was synthesized via a facile hydrothermal method and applied as an anode material in lithium-ion batteries (LIBs). Using this method, Ag nanoparticles (Ag NPs) were embedded in NPC through thermal decomposition of AgNO3 in the pores of NPC. The reversible capacity of Ag-NPC remained at 852 mAh g−1 after 200 cycles at a current density of 0.1 A g−1, showing its remarkable cycling stability. The enhancement of the electrochemical properties such as cycling performance, reversible capacity and rate performance of Ag-NPC compared to the NPC contributed to the synergistic effects between Ag NPs and NPC. Highlights: 1 A novel Ag@nitrogen-doped porous carbon (Ag-NPC) composite was applied to lithium-ion batteries. The encapsulation of Ag nanoparticles (Ag NPs) into NPC boosts reversible capacity from 501.6 to 852 mAh g−1. 2 Ag-NPC shows a much better cycling performance than NPC due to the synergistic effect of NPC and Ag NPs.